The modern principle of statutory interpretation - Hutchison, Cameron (LexisNexis, 2022)
"This book analyzes the modern principle of statutory interpretation as described by Canadian courts. An invaluable resource, the book includes the topic from an administrative law perspective, as well as constitutional interpretation."– Provided by publisher.